2017
DOI: 10.5812/ijcm.15087
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Back Pain in Colon Cancer: A Case Report

Abstract: Introduction: The research evidence supports the effectiveness of acupuncture as an alternative or supplementary therapy for back pain and some of musculoskeletal pains. On the other hand, the use of opioids in the management of cancer pain is common. The effectiveness of acupuncture on the amount of pain and the level of cortisol in opioid-dependent patients has not been addressed so far. Case Presentation: A 54-year-old man with metastatic cancer under chemotherapy and methadone maintenance treatment after 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results showed that four weeks of acupuncture treatment decreased the salivary cortisol level as the primary outcome and suicidal ideation as the secondary outcome. Consistent with the results of the primary outcome in the present study, Pirnia et al (6) reported that the use of acupuncture leads to the regulation of HPA axis activity in a case with colon cancer. Guo et al (5) showed that acupuncture has a significant effect on the level of morning salivary cortisol.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that four weeks of acupuncture treatment decreased the salivary cortisol level as the primary outcome and suicidal ideation as the secondary outcome. Consistent with the results of the primary outcome in the present study, Pirnia et al (6) reported that the use of acupuncture leads to the regulation of HPA axis activity in a case with colon cancer. Guo et al (5) showed that acupuncture has a significant effect on the level of morning salivary cortisol.…”
Section: Discussionsupporting
confidence: 91%
“…Breast cancer is the most common cancer among women worldwide, but it is one of the most treatable cancers as well. It is common and curable and a large number of patients are treated and have long lifetimes; so, they require support after diagnosis and during and after treatment (1). Regarding the nature of cancer, psychological and complementary therapies play an important role in the management of this disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…After treatment, 64% of the patients reported moderate pain relief and 71% reported moderate stress relief. Pirnia et al [17] in their case report pointed to the improvement of back pain caused by the increase of the cortisol levels of the patient with colon cancer. Another effect was the aid in xerostomia in the Morganstein study [18], this one pointed out that acupuncture increased salivary production, but did not reach equal levels before irradiation, patients also had improvement in physical, emotional and cognitive well-being influencing positively in the QV.…”
Section: Acupuncture As An Intervention For the Side Effects Of Cancer And Treatmentmentioning
confidence: 97%